2023
DOI: 10.3390/agriculture13061268
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Research on Cotton Stalk Cutting and Crushing Based on ANSYS/LS-DYNA and Field Experiments

Abstract: In order to solve the problem of high straw content in recovered residual film and the low rate of qualified straw crushing in combination with a front-mounted cotton-straw-crushing device, the cutting and crushing mechanisms of cotton stalks were studied based on ANSYS/LS-DYNA. The height h and dip angle α of the fixed blade were determined to be 30 mm and 75° through a finite element analysis. On the basis of the device design, explicit dynamic models of the cutting and crushing of a single cotton stalk were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Niu et al [17] designed a corn straw crushing and scattering device, and through simulation tests and physical tests, they determined that when the crushing knife shaft speed is 700 r/min, the device has better working performance and the corn straw crushing qualification rate is 93.65%. Wang et al [18] studied the cutting and crushing mechanism of cotton straw based on ANSYS/LS-DYNA 13.0. The results showed that when the rotation speed was 1800 r/min, the crushing pass rate was 84.6% and the removal rate was 95.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Niu et al [17] designed a corn straw crushing and scattering device, and through simulation tests and physical tests, they determined that when the crushing knife shaft speed is 700 r/min, the device has better working performance and the corn straw crushing qualification rate is 93.65%. Wang et al [18] studied the cutting and crushing mechanism of cotton straw based on ANSYS/LS-DYNA 13.0. The results showed that when the rotation speed was 1800 r/min, the crushing pass rate was 84.6% and the removal rate was 95.1%.…”
Section: Discussionmentioning
confidence: 99%